2015
DOI: 10.1007/978-3-319-23512-7_48
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of European Examples of Freight Electric Vehicles Schemes—A Systematic Case Study Approach with Examples from Denmark, Germany, the Netherlands, Sweden and the UK

Abstract: Continuing in the footsteps of the three previous international conferences on Dynamics in Logistics, LDIC 2014 was the fourth event in this series to be held in Bremen (Germany) from February 10 to 14, 2014. The conference was accompanied by a "Doctoral Workshop" as well as the "InTraRegio International Dialog Event" and the "MAPDRIVER Kickoff Meeting" as satellite events. Similar to its predecessors LDIC 2007, LDIC 2009, and LDIC 2012, the Bremen Research Cluster for Dynamics in Logistics (LogDynamics) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…It was found that there were significant savings in societal costs and total cost of ownership when compared to diesel vehicles (Bor en, 2019). On the other hand, electric motors are less complex propulsion systems than ICV, which means they are less costly to maintain (Taefi et al, 2016). Therefore, the perceived benefit has a positive effect on purchase intention Kim et al, 2018).…”
Section: Context Factorsmentioning
confidence: 99%
“…It was found that there were significant savings in societal costs and total cost of ownership when compared to diesel vehicles (Bor en, 2019). On the other hand, electric motors are less complex propulsion systems than ICV, which means they are less costly to maintain (Taefi et al, 2016). Therefore, the perceived benefit has a positive effect on purchase intention Kim et al, 2018).…”
Section: Context Factorsmentioning
confidence: 99%
“…Environmental, technical, logistic, and financial factors as well as energy supply and infrastructure have especially a major impact on electromobility, as reported by [2][3][4]. As concluded by [5], profitability is the primary reason for major transportation companies to consider the switch-over to electrification.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Sustainable Urban Freight Transport (SUFT), the main idea is to reduce freight traffic in the city centre. A popular solution in that respect is organising local Urban Consolidation Centres (UCCs) [43][44][45], located outside city centres, from which deliveries may be made via, among other things: Electric Freight Vehicles (EFVs), Light Electric Freight Vehicles (LEFVs) [46][47][48][49][50], Small Sized Electric Vehicles (SEVs) [51], or e-cargo bikes [52]. The tasks completed by these vehicles may also be supported by a vehicle category called Non-Motorised Transport (NMT), including cargo bikes/cargo cycles [53,54], cycle rickshaws, or handcarts [55].…”
Section: Literature Reviewmentioning
confidence: 99%